Diagnostic utility of fine needle aspiration cytology in the evaluation of neoplastic cutaneous nodular lesions: experience from tertiary care institute - Soni, Sarita; Mardi, Kavita (International Journal of Research in Medical Sciences, 2020)
Background: Cutaneous nodules can result from neoplastic and non-neoplastic causes. The present study conducted with the aim to find out sensitivity, specificity and diagnostic accuracy of cytology in neoplastic cutaneous nodules. Methods: This prospective study was conducted for a period of one year from August 2017 to August 2018. Nodular skin lesions diagnosed clinically as neoplastic were assessed by Fine needle aspiration cytology (FNAC) and correlated with histopathology. The sensitivity, specificity and accuracy of FNAC were determined using histopathology as a gold standard. Results: 82 cases with nodular skin lesions were subjected to cytological examination and biopsy. Aspiration was inadequate in 03 cases. For diagnosing neoplastic lesions, FNAC had a sensitivity of 98.7%, specificity of 94.6% and diagnostic accuracy of 97.4%. Conclusion: FNAC is safe, rapid, cost effective, highly sensitive and specific for the diagnosis of neoplastic nodular skin lesions with high diagnostic accuracy.